POLEMIK PENYIARAN PUBLIK DI INDONESIA: POTRET KONDISI TVRI: Arlan Firnandi - Jurnal COMMED (Prodi Ilmu Komunikasi Universitas Putera Batam, 2017)
Public service broadcasting (PBS) has a central role in the terminology of the democratic broadcasting system. The role of PBS institutions is aspired to be an information balancing institution by bringing democratic values, plurality, and maintenance the cultural values of society. In Some Countries, Public broadcasting are not always in ideal conditions. Some Problems in internal and pressure from external are the factors that often hinder it. This article try to seeks the picture of condition of PBS in Indonesia, especially TVRI. The discussion is doing by tracing the history of birth and development, the problems present, and the challenges of the future that facing TVRI. This article uses a qualitative descriptive approach by using literature review method. The collecting of data doing by use literature review technique on relevant sources.